Medical Management of Acute Venous Thromboembolism - Wilkins, Cy R.; Chiu, Andrew M.; Kishore, Sirish A. (Seminars in Interventional Radiology, 2025)
Venous thromboembolic disease (VTE) is a major cause of morbidity and mortality worldwide, consisting of both deep vein thrombosis (DVT) and pulmonary embolism (PE). Therapeutic anticoagulation is the primary treatment for acute VTE with the therapeutic goals of reducing proximal DVT embolization, inhibiting propagation or formation of new or recurrent VTE, and reducing mortality in patients with PE. Direct oral anticoagulants (DOACs) are now considered first-line therapy for most patients with acute VTE, though parenteral therapy and vitamin K antagonist (VKAs) remain as the preferred option in select patient groups. This study practically summarizes the medical management of acute VTE for interventionalists, focusing on the choice of agent amongst common pharmacologic therapies as well as the optimal duration of therapy based on risk factors for recurrent VTE.
Keywords: venous thromboembolism; medical management; anticoagulation; direct oral anticoagulants; heparin; interventional radiology